2021
DOI: 10.1109/jsen.2021.3061623
|View full text |Cite
|
Sign up to set email alerts
|

Land and Underwater Gait Analysis Using Wearable IMU

Abstract: Walking underwater reduces joint impacts, enhances stability and lowers the net body weight of the patient during rehabilitation. It is a recent rehabilitation method and few suitable methods exist to study underwater gait kinematics. We propose an underwater inertial measurement (IMU) system analogous to those used in land-based rehabilitation to investigate gait kinematics. The objective of this study was to test and validate the proposed system in two human trials by evaluating the knee angle during the gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Table 1 summarizes the characteristics and demographics of the included articles, showing that the majority of studies were published between 2017, 31 38 2019 39 42 and 2020 43 46 and no articles were found before 2014. Most of the articles 31 33 , 35 37 , 42 , 44 51 involved healthy adults or elderly subjects, 41 , 43 while the remaining investigated anterior cruciate ligament injury, 34 , 52 incomplete spinal cord injury 39 , 40 , 53 and chronic anterior knee pain. 38 Three studies involved a healthy control group, 34 , 38 , 39 and one 52 exploited previously published data of a healthy reference group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the characteristics and demographics of the included articles, showing that the majority of studies were published between 2017, 31 38 2019 39 42 and 2020 43 46 and no articles were found before 2014. Most of the articles 31 33 , 35 37 , 42 , 44 51 involved healthy adults or elderly subjects, 41 , 43 while the remaining investigated anterior cruciate ligament injury, 34 , 52 incomplete spinal cord injury 39 , 40 , 53 and chronic anterior knee pain. 38 Three studies involved a healthy control group, 34 , 38 , 39 and one 52 exploited previously published data of a healthy reference group.…”
Section: Resultsmentioning
confidence: 99%
“…This variety is also reflected in the adopted protocols, exercises and evaluation metrics. Gait analysis is performed on dry land and underwater in nine studies, 34 , 42 , 43 , 45 49 , 51 , 52 following in four 34 , 43 , 48 , 52 cases the Outwalk protocol. 54 In all of these works, as well as in studies evaluating running on a treadmill, 32 , 33 the measured outcomes are focused on temporo-spatial parameters, joint kinematics and range of motion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this study compared the outcomes of artificial neural network (ANN), Gaussian process, k-nearest neighbor (kNN), linear regression, and support vector regression (SVR) for the proposed method. These five machine learning algorithms were selected given their frequent use for wearable systems in previous studies [ 32 , 33 , 34 , 35 , 36 ]. In addition, ANN, Gaussian process, kNN, and SVR were expected to build regression models for nonlinear and complex data distribution [ 37 , 38 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sensors are small and light and can capture human motion outside a laboratory environment. Several studies have demonstrated the accuracy and reliability of the IMU for gait analysis [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%